ANALYSIS OF STUDENT ERRORS IN COMPLETING MATHEMATICS UNDERSTANDING QUESTIONS IN MATHEMATICS CAPITA SELECTA COURSE - Rani Sugiarni; Nia Jusniani; Widy Nugraha M. (Departemen Pendidikan Matematika, FPMIPA, UPI, 2022)
The purpose of this study was to determine the students' mathematical understanding ability in understanding social arithmetic material in terms of high, medium, and low levels, to find out what errors were experienced by students in solving problems of mathematical understanding ability, and to determine the factors that caused students to often make mistakes on ability questions. Mathematical understanding in Capita Selecta Mathematics courses. The type of research used is descriptive quantitative research. The subjects in this study were level I students of the mathematics education study program in Cianjur Regency for the 2019/2020 academic year. Tests and interviews are used as data collection techniques. The instruments used are a test of mathematical understanding ability and indirect interviews. The results of the students' mathematical understanding ability test in understanding social arithmetic material in terms of high, medium, and low-level abilities show that students still make mistakes in solving mathematical understanding problems on social arithmetic problems, both students with high, medium, and low criteria. While the mistakes that are often experienced by dominant students make errors using data, besides that, some students still have conceptual and technical errors, and the main factors causing students to make mistakes are lack of accuracy and difficulty in understanding what is contained in the questions. Keywords: analysis, error, mathematical understanding, social arithmetic.